Assesing community readiness for smart city development in sragen using POER framework - Merlin Swantamalo Magna; Ulfah Sulistyowati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
This study aims to analyze the level of readiness of the people of Sragen Regency in supporting the implementation of Smart City through the use of Disdukcapil digital services using the Perceived Organizational E-Readiness (POER) framework. The study uses a descriptive quantitative approach through a survey of 100 respondents who are users of Disdukcapil services, with the sample determined using the Cochran formula because the population size is unknown. Data were collected through a valid and reliable Likert scale questionnaire, then analyzed descriptively and using simple inferential statistics. The results show that community readiness is in the middle category with disparities between dimensions, where Awareness and Business Resources are fairly ready, while Human Resources are still not ready. The low Human Resources dimension is reinforced by the high percentage of technical constraints and low problem-solving skills. These findings indicate to have that community readiness has not progressed evenly and remains relatively passive. Consequently, the success of Sragen Smart City requires to have a strategy that not only focuses to have on strengthening technological aspects but also emphasizes to have the continuous enhancement of community capacity and digital literacy to realize to have an inclusive and participatory Smart Society.